Relationship of Initial Lactate Dehydrogenase (LDH) with initial tumor load and bone marrow remission in childhood Acute Lymphoblastic Leukemia (ALL) (Community Based Medical Journal, 2013)
This was a prospective interventional study conducted in the department of pediatric hematology and oncology in BSMMU during the period from January 2004 to June 2005. The objectives of the study were to observe- The effects of initial tumor load on initial LDH and the relation of initial LDH levels with response to remission induction chemotherapy in childhood ALL.  All the children from one to fourteen years with the confirmed diagnosis of ALL, irrespective of their sex, were included in the study. Out of total 40 cases 21 of them were male and 19 female. As much as 60% of them were from rural areas and 40% city dwellers. Before starting chemotherapy for induction of remission complete clinical and laboratory assessments were done. Evaluation was also performed on 7th, 14th, 21st and 28th days after the starting of treatment. All the assessments were done to see whether the cases were in bone marrow remission or not.  Initial LDH level was found to have direct correlation with initial WBC as well as initial blast cell count. Mean LDH levels differed significantly between the group having initial hyperleukocytosis (50x10(9)/L) and that below 50x10(9)/L. Mean LDH level was also significantly higher in the cases of ALL with IBC >25x10(9)/L than the group with IBC below 25x10(9)/L.  The cases with very high initial LDH level responded poorly to dexamethasone monotherapy as well as to polychemotherapy in induction of remission in childhood ALL. Level of initial LDH was observed to be a significant indicator of outcome of induction of remission in childhood Acute Lymphoblastic Leukemia. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14174 Community Based Medical Journal Vol.2(1) 2013 3-8